Information Portal of the Diversified Structure of High-Tech Business as a Complex Object of Copyright in the Virtual Space - GUMEROVA, Gjusel I.; SHAIMIEVA, Elmira Sh. (Journal of Advanced Research in Law and Economics, 2017)
In this study are generated: methodological support of management of high-tech business (conceptual framework, the classification of enterprises), methodological support of the information portal as an object of management of enterprises of high-tech businesses. The paper examines the institutional provisions of the information portal as part of a multimedia product as a complex object of copyright; formed the definition of ‘information portal’ as part of a multimedia product, its characteristics in conjunction with the virtual property in the broad, narrow sense; the structure of the information portal highlighting the mandatory and optional parts; conducted case studies of seven portals of foreign and Russian enterprises of high-tech business, which as a diversified structures operating in high,- middle-tech kind of economic activities, and also in the field of knowledge-intensive services; carried out diagnostics of the official website of the company at the twenty-one criteria in a mandatory, additional parts of an information portal; developed the site of a diversified structure with the using of tools of strategic management (strategic management areas, product portfolio). The empirical base of the research are the official sites of the diversified high-tech business structures of Germany, Russia, USA. The study extended and confirmed the hypothesis about the activity, product portfolio diversified structures of high-tech business. As a result the study developed the concept of ‘enterprise high-tech business’ based on rankings of Thomson Reuters (USA) and ‘TekhUspekh’ (Russia); developed the concept of the 'information portal of the enterprise high-tech business’ as part of a multimedia product as a complex object of copyright; the structure of the information portal of the enterprise of high-tech business as the object of its management in the virtual space; developed recommendations to management of the JCS ‘Zawod Elecon’ (Kazan, Russia) in the field of information portal.